Health-related physical fitness in children among five Mediterranean countries: a cross-cultural study from the DELICIOUS project - Aly, Mohamed; El-Gyar, Noha; Shalaby, Amira M.; Abdelkarim, Osama (Frontiers in Public Health, 2025)
BackgroundHealth-related fitness (HRF) components are essential for supporting healthy growth and reducing long-term health risks in children. This study explored cross-cultural variations in HRF among children from five Mediterranean countries—Egypt, Italy, Lebanon, Portugal, and Spain—within the framework of the DELICIOUS project.MethodsA total of 860 children participated in the study, including 204 from Egypt (n = 204, 11.72 ± 1.46 years), 150 from Italy (9.66 ± 1.10 years), 200 from Lebanon (10.73 ± 1.90 years), 181 from Portugal (11.04 ± 1.83 years), and 125 from Spain (12.33 ± 2.27 years). Participants completed the International Physical Performance Test Profile (IPPTP), which assesses sprint speed (20 m dash), coordination (jumping sideways), upper body strength (push-ups), abdominal strength (sit-ups), lower body power (standing long jump), and cardiovascular endurance (6-min run). Children were categorized into two age groups: 8–10 and 11–14 years. ANCOVA, adjusting for BMI, was performed to analyze differences across countries and age groups.ResultsAnalysis revealed significant differences in HRF across countries and age groups (p < 0.05). Spanish boys and girls consistently demonstrated superior sprint performance (20 m dash) and cardiovascular endurance (6-min run) compared to peers from other countries. Lebanese and Spanish girls exhibited stronger abdominal performance (sit-ups) than Egyptian girls, while Spanish girls also excelled in lower-body power (standing long jump). These findings underscore cross-cultural variations in HRF outcomes among Mediterranean children.ConclusionCross-cultural differences in physical education programs and sports participation appear to influence HRF in children across the Mediterranean region. These findings underscore the need for culturally tailored physical education strategies and public health initiatives to ensure balanced fitness development in diverse cultural populations.